Modern Competencies of Genetic Systems of Biological Substances in Patients with Caries Disease - Kolenko, Ю. Г.; Zelinska, Н. А.; Viderska, Г. В. (Actual Dentistry, 2026)
Relevance. Dental caries remains one of the most common diseases in humans and is second only to cardiovascular diseases. This is due to the lack of a clear understanding of the etiopathogenetic cause-and-effect relationships. Objective: to determine the place of competence of genetic markers of biological substances of blood and saliva in the etiopathogenesis of caries. Materials and methods. The study of group-specific blood factors as potential genetic markers of dental caries was conducted in 916 individuals. The determination of genetic markers in blood and saliva was performed using hemagglutination reactions. Results of the study. It was found that the risk of dental caries is quite high in Bα(III) carriers. It was found that the presence of the B antigen in saliva can be considered a risk factor. We have established a correlation between dental caries and the presence of Lewis antigens in saliva. In general, the following genotypes were classified as ‘critical’: Le(a–b+) P1+ , Le(a–b–)P1+ , Le(a–b+)M, Rh+(D)M, MP1+ , MP1–, Rh+ P1+, Rh– P1+. The protective combinations of erythrocyte antigens included the phenotypes Le(a+b–), Le(a–b+)Р1–, Le(a–b–)Р1–, Le(a+b–)Rh+, Le(a+b–)МN, Le(a–b–)N, Rh+МN, Р1–МN, Rh+Р1–, Le(a–b+)N, Р1–N, which were 2–4 times less frequent in patients with dental caries. Conclusions. Critical phenotypes of the systems were established Р1+, М, Rh–, Le(a–b+) in patients with caries, protective ones — Р1–, N, NМ, Rh(D), Le(a+b–), which are more common in healthy people. For the first time, the existence of equiaxed phenotypes (Le(a–b–)) was proven, which are equally common in both patients and healthy people. The data obtained allow us to scientifically define risk groups, enabling a tailored therapeutic and preventive approach for different categories of people. A substantive view of the role and place of immunogenetic research in dentistry is proposed.